2022
DOI: 10.3390/agronomy12112820
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Nutrient Solution and Dose for the Yield of Nuclear Seed Potatoes under Aeroponics

Abstract: The aeroponic production of certified seed potatoes is a booming alternative for arid and semi-arid areas where fresh water is scarce and soil-borne diseases and nematodes preclude field production. Although widely used in aeroponics, nutrient-solution salinity effects have not been evaluated in potatoes. This study aimed to (1) establish the best of two nutrient solutions (Otazú vs. modified Furlani) at 20, 50, 100, and 150% of the crop-recommended dose for seed-potato production, (2) evaluate growth indexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The obtained results of a high number of minitubers in aeroponics are in line with previous studies (Rykaczewska, 2016;Bucksetha et al, 2016;Khalil & Hamed, 2020;Silva Filho et al, 2022). Furthermore, aeroponics produced up to three times more tubers than soil substrates (Rykaczewska, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained results of a high number of minitubers in aeroponics are in line with previous studies (Rykaczewska, 2016;Bucksetha et al, 2016;Khalil & Hamed, 2020;Silva Filho et al, 2022). Furthermore, aeroponics produced up to three times more tubers than soil substrates (Rykaczewska, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The nutrient solution is one of the most important factors affecting potato mini-tuber production in aeroponics (Silva Filho et al, 2022). Nitrogen is one of the most important nutrients that control potato growth, and reducing nitrogen reduces the number of tubers produced while increasing nitrogen delays tuberization and extended vegetative growth (Souza et al, 2013;Oraby et al, 2015;Chang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as stated by Otazú [1], the NH 4 NO 3 content in the nutrient solution decreased by 50% 36 days after transplanting (Table 1). Research by Silva Filho et al [23] showed that this nutrient solution consistently kept the salt level below the crucial threshold for potato plants. The nutrient solution used in this study was calculated using the principle of cationanion balance [28].…”
Section: Nutrient Solutionmentioning
confidence: 96%
“…Aeroponics produces virus-free mini-tubers under controlled greenhouse conditions and plant morpho-physiological parameters can be correlated with plant tuber yield and fresh weight [21,22]. If these indices are also used to predict regular potato tuber production, they can help growers and researchers estimate edible potato-tuber yield under aeroponics [23].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment T 6 containing (18g NPK and 6g micronutrient) respectively recorded highest plant spread i.e., (26.43). As aeroponic systems, with their carefully maintained pH levels, allowed plants to quickly and efficiently absorb all of the nutrients they needed to grow [12]. The treatment (T 6 containing 18g NPK and 6g Micronutrient) respectively recorded highest root length at 30, 60, 90 and 120 days of observation i.e., (28.35) The greatest root length may be attributable to an abundance of phosphorus, which stimulates root expansion [13].…”
Section: Effect Of Different Concentration Of Major and Micro Nutrien...mentioning
confidence: 99%